OP0134 Long term outcome and prognosis factors of complications in takayasu's arteritis: multicenter study of 318 patients. (15th June 2017) - Comarmond, C; Biard, L; Lambert, M; Mekinian, A; Ferfar, Y; Kahn, J-E; Benhamou, Y; Chiche, L; Koskas, F; Cluzel, P; Hachulla, E; Messas, E; et al.
Abstract : Objectives: To assess long term outcome and to elaborate a prognostic score for vascular complications in patients with Takayasu arteritis (TA). Methods: Retrospective multicenter study of characteristics and outcome of 318 TA patients [86% of females; median age 36 [25–47] years; median follow-up of 6.1 years] fulfilling ACR and/or Ishikawa criteria. Factors associated with the event free survival (EFS), relapse free survival (RFS) and incidence of vascular complications were assessed. A prognostic score for vascular complications was elaborated based on a multivariate model. Results: The 5- and 10-years event free survival (EFS), relapse free survival (RFS) and complication free survival were 48.2% (42.2;54.9) and 36.4% (30.3;43.9), 58.6% (52.7;65.1) and 47.7% (41.2;55.1), and 69.9% (64.3;76) and 53.7% (46.8;61.7), respectively. Progressive disease course (p=0.018) and carotidodynia (p=0.036) were independently associated with EFS. Male gender (p=0.048), elevated C reactive protein level (p=0.013), and carotidodynia (p=0.003) were associated with RFS. Progressive disease course (p=0.017), thoracic aorta involvement (p=0.009), and retinopathy (p=0.002) were associated with complication free survival. We define high risk patients for vascular complications according to the presence of two of the following factors (i.e a progressive clinical course, thoracic aorta involvement and/or retinopathy). The probability of complication free survival at five years was 78.4% (69.4;88.6) and 51.5% (38.3;69.2) in the low risk and high risk group, respectively. Conclusions: This nationwide study shows that 50% of TA patients will relapse and experience a vascular complication at 10 years. We could define high risk TA patients for vascular complications. Disclosure of Interest: None declared